Participatory photography project - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS and CIAT conducted a Participatory Photography project with youth in Chiquimula, Guatemala and Puno, Peru. The objective of the project is to build a bridge between local voices and research institutions and policy makers to encourage the inclusion of local needs, wants and knowledge on climate change and agriculture of the next generation of farmers.